Neuroendoscopic-assisted versus mini-open craniotomy for hypertensive intracerebral hemorrhage: a retrospective analysis - Wenchao Lu (BMC Surgery, 2022)
Abstract Objective To compare outcomes in neuroendoscopic-assisted vs mini-open craniotomy for hypertensive intracerebral hemorrhage (HICH), so as to provide reasonable surgical treatment. Methods Clinical data of 184 patients with HICH in the hospital from January 2019 to May 2021 were analyzed retrospectively. The patients were divided into mini-open craniotomy group and neuroendoscopic-assisted group. The operation time, hematoma clearance rate, intraoperative blood loss, neurological function recovery, and postoperative mortality of the two groups were compared by retrospective analysis. Results The operation time and intraoperative blood loss in the mini-open craniotomy group were more than those in the neuroendoscopic-assisted group, but there was no significant difference between the two groups. There was no significant difference in hematoma clearance rate between the two groups, but for the rugby hematoma, the hematoma clearance rate in the neuroendoscopic-assisted group was higher than in the mini-open craniotomy group, the difference was statistically significant. Within 1 month after the operation, there was no significant difference in mortality between the two groups. 6 months after the operation, there was no significant difference in the recovery of neurological function between the two groups. Conclusion Neuroendoscopic-assisted and mini-open craniotomy for the treatment of HICH has the advantages of minimal trauma with good effects, and its main reason for short operation time, reduced bleeding, and high hematoma clearance rate. Although the two surgical methods can improve the survival rate of patients, they do not change the prognosis of patients. Therefore, the choice of surgical methods should be adopted based on the patient's clinical manifestations, hematoma volume, hematoma type, and the experience of the surgeon.